2023
DOI: 10.1128/spectrum.01155-23
|View full text |Cite
|
Sign up to set email alerts
|

Robust Vaccine-Induced as Well as Hybrid B- and T-Cell Immunity across SARS-CoV-2 Vaccine Platforms in People with HIV

Abstract: Some studies have suggested that people with HIV may respond less well to vaccines against SARS-CoV-2. We comprehensively compared B- and T-cell responses to different COVID-19 vaccines in middle-aged persons with well-treated HIV and individuals of the same age without HIV, who were also highly comparable in terms of demographics and lifestyle, including those with prior SARS-CoV-2 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Hybrid immunity is thought to specifically enhance Omicron variant neutralization. Verburgh et al compared severe SARS-CoV-2 vaccine-induced and hybrid B-cell and T-cell responses in middle-aged PWH vs. HIV-negative controls who were highly comparable in terms of demographics and lifestyle [ 18 ]. PWH mounted equally robust immunity following vaccination and even more robust stronger immunity was observed in both groups following naturally acquired SARS-CoV-2 infection [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid immunity is thought to specifically enhance Omicron variant neutralization. Verburgh et al compared severe SARS-CoV-2 vaccine-induced and hybrid B-cell and T-cell responses in middle-aged PWH vs. HIV-negative controls who were highly comparable in terms of demographics and lifestyle [ 18 ]. PWH mounted equally robust immunity following vaccination and even more robust stronger immunity was observed in both groups following naturally acquired SARS-CoV-2 infection [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Verburgh et al compared severe SARS-CoV-2 vaccine-induced and hybrid B-cell and T-cell responses in middle-aged PWH vs. HIV-negative controls who were highly comparable in terms of demographics and lifestyle [ 18 ]. PWH mounted equally robust immunity following vaccination and even more robust stronger immunity was observed in both groups following naturally acquired SARS-CoV-2 infection [ 18 ]. Meanwhile, Lu et al examined humoral longitudinal observational study in PWH following primary inactivated SARS-CoV-2 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…However, information on mRNA vaccine immunogenicity in immunocompromised individuals is still limited. Prospective large-scale, longitudinal cohort studies can provide comprehensive health, behavioral, epidemiologic, and socioeconomic data to analyze the impact of HIV-related immunosuppression and other comorbidities on immunogenicity to mRNA vaccines [3,4]. Nested into two large national cohorts, namely the Swiss HIV Cohort Study (SHCS) [4] and the Swiss Transplant Cohort Study (STCS) [5], the COrona VaccinE tRiAL pLatform (COVERALL) [6] was initiated to determine noninferiority of the Moderna mRNA-1273 to the Pfizer-BioNTech BNT126b2 vaccine in immunocompromised patients after basic immunization (COVERALL-1) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, multiple studies used anti-spike antibody assays and live-virus NTs containing the WT to quantify humoral immune responses to infections and monovalent vaccinations in PLWH and demonstrated that antibody levels in immunological responders to antiretroviral treatment were similar to non-HIV-infected individuals [6][7][8][9][10][11][12]. Conversely, low antibody concentrations were found in PLWH with low CD4 numbers and a discordant immune response to retroviral therapy [13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in people living with HIV (PLWH), the humoral immunity to SARS-CoV-2 mRNA vaccinations in terms of neutralizing capabilities and total levels of spike-specific antibodies may be weaker. However, the immune response to the vaccinations must not necessarily be impaired when the CD4+ T-cell counts are not significantly decreased [6][7][8][9][10][11][12]. Accordingly, PLWH with lower CD4+ T-cells or a discordant immune response to antiretroviral therapy display weaker antibody responses after SARS-CoV-2 vaccinations, calling for an exact antibody assessment and additional vaccinations in these individuals [13][14][15].…”
Section: Ofmentioning
confidence: 99%